ANALISIS BAKTERI KOLIFORM DAN PATOGEN DEPOT AIR MINUM KECAMATAN MANDONGA KOTA KENDARI - Aswan, Muhammad Aswan; Darlian, Lili; Yanti, Nur Arfa (Prosiding Seminar Nasional Riset Kuantitatif Terapan 2017, 2017)
Refill drinking water depot used primarily in sub-district community Mandonga. Which is indicative of contamination of drinking water refill that contamination of coliform bacterial and pathogenic bacteial. The aim of the study was to determine the microbiological quality of drinking water refill in District Mandonga. In this work, carry out were analyzed technique quantitatively and qualitatively by testing the Presumtive test, Confirmed test and Complied test as well as using specific media. The result suggest that, there is a negative one, namely coliform bacterial from the village and there are four depots Anggilowu positive coliform bacterial that is depot in the village of Alolama, Wawombalata, Labibia and Korumba, with the highest MPN value found in the depot Korumba and Wawombalata is > 1100 MPN/100 mL, whereas in the Alolama village is 240 MPN / 100 mL and in the Wawombalata village is 460 MPN/ 100 mL to MPN a value. The result of indicate that bacterial amplifier contamintaion of the depot is a non-faecal colifom bacteria (Enterobacter). Based on the test result found pathogenic bacteria Vibrio sp. at the depot in the village Alolama, Wawombalata and Labibia.Keywords— Coliform Bacterial, Pathogen, The Quality of Drinking Water Depots